Learning Media "ARASIK" in Understanding the Meaning of Nouns for SDLB Deaf Students at SLB Negeri Bogor - Santika, Siti Sarah; Imas Diana Aprilia; Budi Susetyo (Proceeding of International Conference on Special Education in South East Asia Region, 2024)
Deaf children experience speech and language difficulties due to hearing loss. Children with hearing loss experience delays and communication difficulties due to delays in speech and language development. The main problem in language acquisition for deaf children is that they have difficulty understanding the meaning of words. The problem is that children can read, but they do not understand what they read. The title of this article is ``The learning media "ARASIK" in understanding the meaning of nouns in SDLB Deaf students at SLB Negeri Bogor" The theoretical foundations used in this study are: (1) understanding the meaning of words, as stated by Nurbeiti Jamalus that the meaning of a word is the relationship between the sound (language) of the word spoken or written with the object concerned; (2) Augmented Realitiy learning media promoted by scientists, that AR can visualize abstract concepts for understanding and the structure of an object model allows AR as a more effective media in accordance with the objectives of learning media. This research uses a descriptive-qualitative approach, with data collection techniques through observation, interviews and documentation studies. The data analysis technique used refers to Miles and Huberman (1994) which includes three activities, namely: (1) data reduction, (2) data presentation, and (3) conclusion drawing from the application of "ARASIK" media. Based on the results of the study, it can be concluded that the "ARASIK" media can help facilitate SDLB Deaf students in understanding the meaning of nouns.